Custo de falência em empresas aéreas: o caso da VARIG S.A. - Haar Júnior, Rolf (Universidade do Vale do Rio do Sinos, 2008)
This research makes an empirical investigation about the indirect bankruptcy costs of the company VARIG SA. Some authors consider the relevance of the bankruptcy cost one of the issues that have not been solved in the Financing Theory and, if at any time, these costs are higher than their benefits, their impact on the capital structure become a determiner on the choice of the optimal capital structure. This study proposes an innovation, which is to measure the bankruptcy from the breakpoint test structure. As a result, the indirect costs of VARIG’s bankruptcy demonstrate that these figures were significantly higher than the other figures found by other authors, having been found average 400% by the two procedures adopted. The estimated market value for the company analyzed deteriorated significantly as the petition of the judiciary recovery approached.
Keywords: custo das dificuldades financeiras; custos indiretos de falência; VARIG; custos de falência; financial difficulty costs; indirect bankruptcy costs; bankruptcy costs; Ciências Sociais Aplicadas